Painful procedures and analgesia in the NICU: what has changed in the medical perception and practice in a ten-year period? - Ana Claudia Yoshikumi Prestes; Rita de Cássia Xavier Balda; Gianni Mara Silva dos Santos; Ligia Maria Suppo de Souza Rugolo; Maria Regina Bentlin; Mauricio Magalhães; Paulo Roberto Pachi; Sergio Tadeu Martins Marba; Jamil Pedro de Siqueira Caldas; Ruth Guinsburg (Elsevier, 2016)
Objective: To compare the use of analgesia versus neonatologists' perception regarding analgesic use in painful procedures in the years 2001, 2006, and 2011. Methods: This was a prospective cohort study of all newborns admitted to four university neonatal intensive care units during one month in 2001, 2006, and 2011. The frequency of analgesic prescription for painful procedures was evaluated. Of the 202 neonatologists, 188 answered a questionnaire giving their opinion on the intensity of pain during lumbar puncture, tracheal intubation, mechanical ventilation, and postoperative period using a 10-cm visual analogic scale (VAS; pain >3 cm). Results: For lumbar puncture, 12% (2001), 43% (2006), and 36% (2011) were performed using analgesia. Among the neonatologists, 40-50% reported VAS >3 for lumbar puncture in all study periods. For intubation, 30% received analgesia in the study periods, and 35% (2001), 55% (2006), and 73% (2011) of the neonatologists reported VAS >3 and would prescribe analgesia for this procedure. As for mechanical ventilation, 45% (2001), 64% (2006), and 48% (2011) of patient-days were under analgesia; 56% (2001), 57% (2006), and 26% (2011) of neonatologists reported VAS >3 and said they would use analgesia during mechanical ventilation. For the first three post-operative days, 37% (2001), 78% (2006), and 89% (2011) of the patients received analgesia and more than 90% of neonatologists reported VAS >3 for major surgeries. Conclusions: Despite an increase in the medical perception of neonatal pain and in analgesic use during painful procedures, the gap between clinical practice and neonatologist perception of analgesia need did not change during the ten-year period. Resumo: Objetivo: Confrontar o uso de analgesia versus a percepção de neonatologistas quanto ao emprego de analgésicos para procedimentos dolorosos nos anos de 2001, 2006 e 2011. Métodos: Coorte prospectiva de todos recém-nascidos internados em quatro unidades universitárias. Avaliou-se a frequência do emprego de analgésicos para procedimentos dolorosos por um mês dos anos de estudo. Dos 202 neonatologistas atuantes nas unidades nos três períodos, 188 assinalaram em escala analógica visual de 10 cm (dor >3 cm) a intensidade da dor sentida pelo recém-nascido na punção lombar, intubação traqueal, ventilação mecânica e pós-operatório. Resultados: Para PL, 12%, 43% e 36% foram realizadas com analgesia em 2001, 2006 e 2011 e 40-50% dos neonatologistas referiam indicar analgésicos na punção lombar nos três períodos. Na intubação, 30% foram realizadas sob analgesia nos três períodos e 35% (2001), 55% (2006) e 73% (2011) dos médicos diziam indicar analgésicos. Quanto à ventilação mecânica, 45-64% dos ventilados-dia estavam sob analgesia nos três períodos e 56% (2001), 57% (2006) e 26% (2011) dos neonatologistas diziam usar analgésicos. Dos pacientes-dia nos três primeiros dias de pós-operatório, 37% (2001), 78% (2006) e 89% (2011) receberam alguma dose de analgésico, sendo que mais de 90% dos médicos referiam usar analgesia para essa situação. Conclusões: Entre 2001 e 2011, ocorreu aumento no uso de analgésicos para procedimentos dolorosos nas unidades neonatais e uma percepção mais acentuada por parte dos médicos de que o recém-nascido sente dor, mas o lapso entre a prática clínica e a percepção médica quanto à presença de dor persistiu. Keywords: Pain measurement, Pain perception, Pain management, Neonatal intensive care units, Newborn, Palavras-chave: Medição da dor, Percepção da dor, Manejo da dor, Unidades de terapia intensiva neonatal, Recém-nascido